2014
DOI: 10.1111/joic.12147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thoracic Epidural Anesthesia on Cardiac Function and Myocardial Cell Apoptosis in Isoproterenol‐Induced Chronic Heart Failure Rats

Abstract: Our findings suggest that TEA may reduce myocardial apoptosis and decrease extent of structural damage and abnormalities in the myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Additionally, our results indicated that the HTEA + PDTC group showed no obvious myocardial infraction zone and decreased cell apoptosis rate, which indicated that inhibition of mTOR/NF-κB signaling pathway combined with HTEA reduced myocardial cell apoptosis. A study conducted by Ge et al (2014) once demonstrated that HTEA reduced myocardial cell apoptosis, decreased myocardial infraction size and myocardial abnormalities. Another previous study showed that mTOR/NF-κB signaling pathway could act as a mediator to influence cell apoptosis (Han, Zhang, Meng, Cheng, & Wang, 2016).…”
Section: Figurementioning
confidence: 99%
“…Additionally, our results indicated that the HTEA + PDTC group showed no obvious myocardial infraction zone and decreased cell apoptosis rate, which indicated that inhibition of mTOR/NF-κB signaling pathway combined with HTEA reduced myocardial cell apoptosis. A study conducted by Ge et al (2014) once demonstrated that HTEA reduced myocardial cell apoptosis, decreased myocardial infraction size and myocardial abnormalities. Another previous study showed that mTOR/NF-κB signaling pathway could act as a mediator to influence cell apoptosis (Han, Zhang, Meng, Cheng, & Wang, 2016).…”
Section: Figurementioning
confidence: 99%
“…Abnormal cell apoptosis is involved in the pathophysiological abnormalities of the cardiovascular system (Prescimone et al, 2013). The imbalance of apoptosis is related to the mechanism of many stress responses and the accumulation of myocardial apoptosis and the gradual decrease of cell numbers result in the incomplete development of heart function (Ge et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…MF can contribute to cardiac dysfunction in many pathophysiologic conditions [12]. The levels of LVED, LVES, LVEF and LVFS are main indexes of cardiac function [35]. This study showed that TPL improved cardiac dysfunction in MF rats.…”
Section: Discussionmentioning
confidence: 53%